Charting a new path forward for pharmacy residency expansion. Issue 2 (4th January 2023) - McFarland, M. Shawn; Stover, Kayla R.; Bhat, Shubha; Coon, Scott; Cooper, Mandelin; DiDomenico, Robert; Herbert, Sophia; Kessler, Sarah; Lee, Michelle; Maddox, Mary Margaret; Quidley, April Miller; Rhoney, Denise; et al.
Abstract: A core component of the vision of the American College of Clinical Pharmacy (ACCP) for the profession is that most pharmacists will provide direct patient care. Residency training programs are considered a prerequisite to meet the standards and competencies required for pharmacists providing direct patient care. Barriers to residency training expansion are numerous and include, but are not limited to, lack of funding, challenges in meeting accreditation standards for residency programs, limited practice sites, and lack of qualified preceptors. The demand for postgraduate year one (PGY1) and postgraduate year two (PGY2) pharmacy residency training has exceeded position availability over the past 10 years. The American Society of Health‐System Pharmacists (ASHP) Foundation Pharmacy Forecast 2021 predicts pharmacy expansion within ambulatory care, population health, specialty pharmacy, and home care. To promote pharmacy residency expansion and maintenance of pharmacy residency quality, this commentary makes four recommendations with specific actions for consideration: develop preceptors and promote board certification, promote and foster innovation in residency training, expand residency training to address health equity with a focus on rural/underserved areas, and expand nontraditional residency training programs.